Empowerment Program, Entrepreneurial Competence and Business Growth SMEs in Denpasar - I Gede Cahyadi Putra; Putu Kepramareni; Ni Nyoman Ayu Suryandari (AIBPM Publisher, 2019)
The purpose of this study is first to measure the extent of direct influence of empowerment programs on entrepreneurial competence and growth of micro, small and medium enterprises and indirect influence of empowerment program on the growth of SMEs through business competence variable. The second provides recommendations for the implementation of empowerment programs that are more appropriate to the needs of SMEs. The research location in Denpasar City with the number of samples of 100 entrepreneurs who have got the empowerment program. Data analysis technique to test the relationship model between variables is Structural Equation Modeling using Partial least Square program.